2002
DOI: 10.1046/j.1365-294x.2002.01538.x
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal community composition associated with two plant species in a grassland ecosystem

Abstract: Arbuscular mycorrhizal (AM) fungi are biotrophic symbionts colonizing about two-thirds of land plant species and found in all ecosystems. They are of major importance in plant nutrient supply and their diversity is suggested to be an important determinant of plant community composition. The diversity of the AM fungal community composition in the roots of two plant species (Agrostis capillaris and Trifolium repens) that co-occurred in the same grassland ecosystem was characterized using molecular techniques. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

40
320
5
8

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(373 citation statements)
references
References 44 publications
40
320
5
8
Order By: Relevance
“…A proposed explanation for the stability of the AM fungi-plant mutualistic association over 450 million years is a trade exchange of resources between partners enforced by embargo by one or both members of the symbiosis (19). Our results do not allow us to reject this hypothesis of sanction, but they also substantiate the hypothesis 0.1 of host-plant preference and competition among AM fungal colonizers (5,6,20). The A. stolonifera root-colonizing bacteria were analyzed from RNA in fraction 7 (unlabeled) and fraction 18 (heavily labeled) of experiment B.…”
Section: Resultscontrasting
confidence: 76%
See 1 more Smart Citation
“…A proposed explanation for the stability of the AM fungi-plant mutualistic association over 450 million years is a trade exchange of resources between partners enforced by embargo by one or both members of the symbiosis (19). Our results do not allow us to reject this hypothesis of sanction, but they also substantiate the hypothesis 0.1 of host-plant preference and competition among AM fungal colonizers (5,6,20). The A. stolonifera root-colonizing bacteria were analyzed from RNA in fraction 7 (unlabeled) and fraction 18 (heavily labeled) of experiment B.…”
Section: Resultscontrasting
confidence: 76%
“…Recent studies show that high diversity is the norm even where plant diversity is low (4)(5)(6). These AM fungi are biotrophs, unable to grow in the absence of a living plant, and often display a broad host range although there is growing evidence for differences in host preference (5)(6)(7)(8). They have been demonstrated to improve plant mineral nutrition (3) and stress resistance (3).…”
mentioning
confidence: 99%
“…These 31 AMF phylotypes, from the soils and roots, would account for around 14% of the known species, given the fact that more than 230 AMF taxa have been described so far (KrĂŒger et al, 2012). The number of detected sequence groups revealed in this study was similar to the study of Vandenkoornhuyse et al (2002b), who found 24 sequence groups with an intensive sampling of two host plant species in a semi-natural grassland in Scotland. However, fewer AMF phylotypes were detected in similar grassland ecosystems using the same molecular approaches.…”
Section: Amf Diversity In the Temperate Steppesupporting
confidence: 80%
“…Arbuscular mycorrhizal plant-fungal symbioses form highly specialized 'nutrient-exchange' structures (vesicles and arbuscules) at the plant-fungus interface and are recognized as being a particularly beneficial group of root endophytes. Plants associating with arbuscular mycorrhizal fungi are typically more competitive and better able to tolerate environmental stresses than are non-mycorrhizal or poorly colonized plants (Biermann and Linderman 1983, Daniell et al 2001, Bianciotto and Bonfante 2002, Vandenkoornhuyse et al 2002, Bonfante 2003, Brundrett 2004, DeBellis and Widden 2006, Greipsson and DiTommaso 2006, Parniske 2008, Shah et al 2010. AMF are also known to provide protection from a variety of microbial pathogens to their host plants (Newsham et al 1994, Borowicz 2001, Klironomos 2002, Pozo and Azćon-Aguilar 2007, Van der Putten et al 2007, Appoloni et al 2008, Mogg et al 2008, KrĂŒger et al 2009, Wehner et al 2009).…”
Section: Introductionmentioning
confidence: 99%